Experimental and Numerical Investigation of Unreinforced Masonry Walls with and without Opening - Doran, Bilge; Karslioglu, Metin; Unsal Aslan, Zeynep; Vatansever, Cuneyt (TAYLOR & FRANCIS INC, 2023)
This paper comparatively addresses the numerical modeling techniques for simulating the nonlinear behavior of unreinforced masonry (URM) walls. An experimental test program including two specimens with and without opening was conducted to document the behavior of the specimens. Both specimens were subjected to constant axial load and monotonically increasing in-plane lateral load during the tests. Two different modeling approaches, macro and detailed micro modeling, were considered to develop the finite element models (FEMs) of URM walls. The numerical simulation was performed using ABAQUS finite element software. The results of both modeling strategies were compared with experimental results in terms of the lateral load-displacement response and crack pattern of URM walls. Based on the comparison, the approaches implemented for numerical analyses are found reasonably applicable for simulating the in-plane response of URM walls with and without opening under lateral load.
Keywords: Cohesive interface model; detailed micro modeling; finite element analysis; macro modeling; opening; unreinforced masonry wall; PLASTIC-DAMAGE MODEL; CLAY BRICK MASONRY; SHEAR WALLS; INTERFACE ELEMENTS; INPLANE; BEHAVIOR; FRACTURE; MICROMODEL; CAPACITY; Architecture; Construction & Building Technology; Engineering